The Influence of Promotion, Brand Image and Product Quality on Purchasing Decisions Through Consumer Trust in Bata Brand Shoe Outlets Mall Cibubur Junction East Jakarta - Uripto, Casto; Lestari, Rahayu (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Based on interviews with 100 consumers who made purchases, there were several problems that influenced consumer confidence and purchasing decisions. some of which influence consumer confidence and purchasing decisions. So this research uses the independent variables promotion, brand image and product quality. The intervening variables are consumer confidence and purchasing decision variables. This research aims to analyze how promotion, brand image and product quality influence purchasing decisions through consumer trust in Bata Brand Shoe products. The sampling method used in this research was non-probability with a purposive sampling technique. The samples collected were 100 respondents who had purchased Bata shoe products at least once. The analytical method used is SEM, namely the outer model test includes convergent validity, AVE, discriminant validity, composite reliability and the inner model includes R-Square, significance test, effect size. The research results show that the direct and indirect effects of promotion, brand image and product quality influence purchasing decisions through consumer trust in Bata brand shoes.